2018
DOI: 10.1111/bjc.12199
|View full text |Cite
|
Sign up to set email alerts
|

Paranoia and interpersonal functioning across the continuum from healthy to pathological – Network analysis

Abstract: Network analyses were used to identify central aspects of persecutory ideation in both clinical and non-clinical samples. Qualitative assessment of clinical and non-clinical networks revealed similar central symptoms and supported a continuum model of paranoia. Central aspects of paranoia, that is, feeling that others have talked about oneself behind one's back, being disappointed by others, and having distressing feelings of being watched by others, were associated with deficits in interpersonal functioning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…Social Functioning Scale (SFS) [51] The SFS is a self-report measure of social and role functioning that is sensitive to functional impairment across the psychosis spectrum [52]. SFS outcomes include a total score and seven subscale scores of social functioning (withdrawal, interpersonal behavior, and prosocial activities) and role functioning (recreation, independencecompetence, independence-performance, and occupation).…”
Section: Methodsmentioning
confidence: 99%
“…Social Functioning Scale (SFS) [51] The SFS is a self-report measure of social and role functioning that is sensitive to functional impairment across the psychosis spectrum [52]. SFS outcomes include a total score and seven subscale scores of social functioning (withdrawal, interpersonal behavior, and prosocial activities) and role functioning (recreation, independencecompetence, independence-performance, and occupation).…”
Section: Methodsmentioning
confidence: 99%
“…Previous network research has relied on cross-sectional models to study psychosis ( Isvoranu et al, 2017 , 2018 ; van Rooijen et al, 2017 ). However, only a few studies included paranoia as an element in the network ( Isvoranu et al, 2016 ; Bell and O’Driscoll, 2018 ; Hajdúk et al, 2019 ). Yet, their findings were heterogeneous (for a discussion, see Contreras et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paranoid delusions are the most common delusions in patients with psychosis (Brakoulias & Starcevic, 2008; Gecici et al, 2010) and also found in lower, but varying levels in the general population (Nuevo et al, 2012). Thus, paranoid delusions are considered as a continuous phenomenon (Bell, Halligan, & Ellis, 2006), with hypothesized similar mechanisms acting in patients with psychosis and in nonclinical individuals (De Sousa, Sellwood, Griffiths, & Bentall, 2019; Hajdúk, Klein, Harvey, Penn, & Pinkham, 2019; Oestreich, Randeniya, & Garrido, 2019).…”
Section: Introductionmentioning
confidence: 99%